HUBUNGAN KUALITAS TIDUR DENGAN KUALITAS HIDUP LANSIA DI PANTI WREDHA BUDHI DHARMA YOGYAKARTA - Listyaningsih, Enik; Ratmawati , Yuni (Jurnal Kesehatan, 2017)
Background: In 2014, the number of elderly in DIY was above national average with percentage of 15%, while national average is 7% (B2P3KS, 2015). Physical problems are experienced by elderly because of the aging process, one of them is sleep disorder. The increasing of physical disorders can cause changes in their quality of life. Research Objective: To know the correlation between quality of sleep and quality of life of elderly at Panti Wredha Budhi Dharma Yogyakarta in 2016. Methods: Correlational study with cross sectional design. Population was 52 elderly who live in Panti Wredha Budhi Dharma. It used purposive sampling with 30 samples. The research instrument used questionnaire that had been modified from PSQI and WHOQOL_BREF. Data were analyzed using Spearman Rank. Results: In this study, p value < ?, ie 0.009 <0.05 means that H0 is rejected and H? is accepted, so there is a correlation between quality of sleep and quality of life of elderly at Panti Wredha Budhi Dharma Yogyakarta in 2016. Conclusion: There is a correlation between quality of sleep and quality of life of elderly at Panti Wredha Budhi Dharma Yogyakarta in 2016. Suggestion: Further researchers are suggested to use observation about quality of sleep and quality of life. Keywords: sleep quality - quality of life – elderly